PENGARUH PENYALURAN KREDIT, TINGKAT SUKU BUNGA DAN KECUKUPAN MODAL TERHADAP PROFITABILITAS PADA PERUSAHAAN PERBANKAN KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2021 - REZKY RAHMADANI, ANGGA; GUSTINA, IRA; YUSRIWARTI, YUSRIWARTI (JURNAL AKUNTANSI DAN KEUANGAN, 2023)
This study aims to determine and obtain empirical evidence of the effect of Lending, BI Interest Rates and Capital Adequacy on Profitability in Conventional Banking companies listed on the Indonesian Stock Exchange in 2019-2021. The process of selecting the sample using purposive sampling. The sample in this study are conventional banking companies listed on the IDX for the 2019-2021 period as many as 27 companies with a total observation period of 3 years so that the total sample is 81 companies. The type of data used in this study is secondary data obtained from the official website of the Indonesia Stock Exchange, namely www.idx.co.id. The analysis technique used is multiple linear regression with the help of the SPSS version 26 program. The results of this study indicate that partially the credit distribution variable has no effect on profitability. The interest rate variable has no effect on profitability. Capital adequacy variable on profitability. Simultaneously Lending, Interest Rates and Capital Adequacy have an effect on profitability